A geoenvironmental application of burned wastewater sludge ash in soil stabilization - AI-Sharif, Munjed M. (2014)
This paper studied the use of burned sludge ash as a soil stabilizing agent. The sludge ash was obtained from a public wastewater treatment plant, and it was burned at 550C. Different percentages of burned sludge ash were mixed with three different types of clayey soil. A laboratory study consisting of Atterberg's limits test, unconfined compressive strength test, standard proctor density test, and swelling pressure test were carried out on samples treated with burned sludge at different percentages by dry weight of the clayey soils. The results show that the addition of 7.5 % of the burned sludge ash by the dry weight of the soil will increase the unconfined compressive strength and maximum dry density and also decrease the swelling pressure and the swell potential of the soil. The addition of percentage higher than 7.5 % by dry weight of the soil decreases both the maximum dry density and the unconfined compressive strength; as a result it showed less effectiveness in stabilizing the soil. The conclusion of this research revealed that the burned sludge ash can be used as a promising material for soil stabilization.